Analisis Daya Dukung Lahan untuk Perencanaan Penggunaan Lahan Pertanian dan Pemukiman di Negeri Tial Kecamatan Salahutu Kabupaten Maluku Tengah - Sri Rahmi; Husen Salampessy; Pieter Kunu (JURNAL PERTANIAN KEPULAUAN, 2021)
This study aims to determine the carrying capacity of agricultural land and settlements in Tial Village, Salahutu Subdistrict, as a control over the agricultural sector and settlement development. This research used a survey method of field activities, including observing and measuring the land's carrying capacity in the field. The study results indicated that Tial Village has a high carrying capacity for settlements due to the land area suitable for settlement and the number of residents in each landform. On the other hand, the carrying capacity of agricultural land is low, so the food supply in Tial Village is classified as low to very low. This fact indicates that there is a dominant influence on residential land cover. It is concluded that every known specific land use suitability can be utilized optimally and sustainably.